2019
DOI: 10.1097/01.nep.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner Role Transition and Identity Development in Rural Health Care Settings: A Scoping Review

Abstract: AIM The purpose of this scoping review was to explore the literature regarding the nurse practitioner (NP) role transition and professional identity development at rural health care settings. BACKGROUND Because of the shortage of primary care providers, NPs are meeting the demand for primary care in rural areas. METHOD Arksey and O'Malley's six-stage methodological framework for scoping reviews guided this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…
An advanced practice nurse (APN) is defined internationally as a nurse who has attained specialist knowledge, makes advanced clinical decisions, and performs an expanded practice role in his or her specific context of practice (International Council of Nurses, 2020). Globally, APNs play various roles in primary care settings, such as managing chronic disease, attending to uncomplex medical issues, and being the sole primary care providers in rural areas (Bryant-Lukosius et al, 2017;Lukewich, Edge, VanDenKerkhof, & Tranmer, 2014;Owens, 2019). Depending on legal and practicing rights, APNs may practice independently or collaboratively with physicians (Fealy et al, 2018).
…”
mentioning
confidence: 99%
“…
An advanced practice nurse (APN) is defined internationally as a nurse who has attained specialist knowledge, makes advanced clinical decisions, and performs an expanded practice role in his or her specific context of practice (International Council of Nurses, 2020). Globally, APNs play various roles in primary care settings, such as managing chronic disease, attending to uncomplex medical issues, and being the sole primary care providers in rural areas (Bryant-Lukosius et al, 2017;Lukewich, Edge, VanDenKerkhof, & Tranmer, 2014;Owens, 2019). Depending on legal and practicing rights, APNs may practice independently or collaboratively with physicians (Fealy et al, 2018).
…”
mentioning
confidence: 99%
“…Continuous remote communication is maintained between professionals and work units, requiring attentiveness and practical communication abilities. This circumstance prompted consideration of the significance of a training program for rural community nurses to provide higher-quality care (Owens, 2019). In his study, Moeckli et al (2021) discovered that medical workers in rural health institutions viewed telehealth as highly beneficial for accelerating the treatment of patients who require referrals to more comprehensive urban health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that using telehealth to provide health services to rural regions is a reasonably reliable regarding quality, coordination, and health service agencies (Owens, 2019). This solution efficiently avoids superfluous services that can be performed at home individually (Moeckli, Gutierrez, & Kaboli, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…17 Although the current practice of NPs in Taiwan is hospital-based only, the multidisciplinary team care model emphasizes greater interprofessional collaboration between physicians and other clinicians, such as NPs, to serve patients' best interests during their hospitalization. 25,26 Autonomy allows NPs to participate in collaborations and to positively influence the health care system. 27 Research has demonstrated that this autonomy is a crucial factor influencing NPs' job satisfaction and outcomes.…”
Section: Discussionmentioning
confidence: 99%